Intensity and periods of summer pruning in 'Abate Fetel' pear tree on two rootstocks Intensidade e Épocas de Poda Verde em Pereira 'Abate Fetel' Sobre Dois Porta-Enxertos - Filho J.L.M. (2012)
Brazil is one of the world's largest importers of European pear. The lack of adapted genetic material and deficiency of management technologies, as well the abortion of flower buds of European cultivars has discouraged producers, causing a decrease on planted areas. The purpose of this study was to establish a summer pruning methodology for the cultivar Abate Fetel aiming the increase of fruit set and control of plant vigor. The study was conducted in Frutirol Agricola Ltd. orchards, placed in Vacaria / RS, harvest of 2006/2007 and 2007/2008. The cultivar Abate Fetel was used on two rootstocks: quince 'Adams' and 'EMC'. Were evaluated the effects of two summer pruning levels on three different periods. Treatments consisted of summer pruning with removal of 1/3 and 2/3 of shoots length, on January, February, March and a control without pruning. The experimental design adopted was randomized blocks with split plots, five replications and two plants per replication. It was concluded that the rootstock 'EMC' induces better vigor control and increases productivity rates for 'Abate Fetel', than quince 'Adams'. The summer pruning with removal of 2/3 of shoots length, regardless the month of realization, increases the productivity of Abate Fetel pear.